2021
DOI: 10.1038/s41467-021-21258-5
|View full text |Cite
|
Sign up to set email alerts
|

EGCG binds intrinsically disordered N-terminal domain of p53 and disrupts p53-MDM2 interaction

Abstract: Epigallocatechin gallate (EGCG) from green tea can induce apoptosis in cancerous cells, but the underlying molecular mechanisms remain poorly understood. Using SPR and NMR, here we report a direct, μM interaction between EGCG and the tumor suppressor p53 (KD = 1.6 ± 1.4 μM), with the disordered N-terminal domain (NTD) identified as the major binding site (KD = 4 ± 2 μM). Large scale atomistic simulations (>100 μs), SAXS and AUC demonstrate that EGCG-NTD interaction is dynamic and EGCG causes the emergence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 82 publications
11
101
2
Order By: Relevance
“…We thought that these direct effects did not play a primary role in vivo, as indicated by our results that mice with colitis treated by rectal EGCG trended to exacerbate colitis. As the most abundant tea polyphenol in green tea, it was likely that the beneficial effects of EGCG were mediated through more than one mechanism [61,62]. Besides the functional SCFAs, previous studies have revealed that some phenolic metabolites from EGCG degradation may play a critical role, alongside other beneficial activities of EGCG, in reducing intestinal inflammatory diseases [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…We thought that these direct effects did not play a primary role in vivo, as indicated by our results that mice with colitis treated by rectal EGCG trended to exacerbate colitis. As the most abundant tea polyphenol in green tea, it was likely that the beneficial effects of EGCG were mediated through more than one mechanism [61,62]. Besides the functional SCFAs, previous studies have revealed that some phenolic metabolites from EGCG degradation may play a critical role, alongside other beneficial activities of EGCG, in reducing intestinal inflammatory diseases [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…SAXS data was collected at the beam line 7A1 at the Cornell High Energy Synchrotron Source (CHESS), with a dual Pilatus 100k detector system (Dectris, Baden, Switzerland), at a single detector position, on July 3, 2019 as described previously 85 . Quartz capillary with a path length of 1.6 mm was used as the sample cell (OD=1.5 mm, wall thickness=10 μm).…”
Section: Methodsmentioning
confidence: 99%
“…Both works directly showed that REST covered broader conformational spaces for intrinsically disordered regions and led to faster convergence compared to either standard MD or T-REMD simulations. REST simulations have also been successfully integrated with experiments to study how cancer-associated mutations and drug molecules may modulate the disordered ensembles of p53-TAD and Aβ peptides in recent years [118][119][120][121].…”
Section: Collective Variables-free Sampling Methods and Optimizationmentioning
confidence: 99%